Embracing Change in the Context of Paternal Postpartum Depression: A Concept Analysis Using the Walker and Avant Method - Shintya, Lea Andy (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
The transition to fatherhood requires significant emotional and behavioral adaptation, yet many fathers experience depression when unable to adjust to their new roles. Understanding